Porosity and permeability alteration around wellbore during injection process - Bataee, M. (American Society of Civil Engineers (ASCE), 2018)
Enhanced oil recovery (EOR) methods were processed to increase the amount of oil extracted from a reservoir after primary and secondary recoveries, typically by injecting water or gas. Fluid injection has been vastly applied in oil wells as a simple and effective EOR method. Rocks are a combination of different materials that exhibit poroelastic response. The amount of stress indexed by pore pressure depends on pore content. Rock stress around a wellbore is a function of wellbore fluid flow. On the other hand, fluid flow is the function of porosity and permeability. Nevertheless, porosity and permeability alter as stress changes. Therefore, a coupling method should be used. The purpose of this study is to propose a model to find corrected stresses and calculate the change in porosity and permeability after injection. This study focuses on wellbore results. Effective parameters, such as pressure, temperature, saturation, and stress, were obtained for the multiphase flow condition using mathematical modeling. Moreover, pressure and saturation are solved using the finite-difference method, whereas the finite-volume method is applied to obtain rock stresses. The iterative coupling method is used to improve the accuracy of results. The results of the study showed how porosity and permeability will change after drilling around the well and how they will increase during injection. The results expressed the corrected distribution of stress values after injection. Porosity and permeability were reduced from their original values after drilling; nonetheless, their values had increased after injection but not equally around the wellbore. Moreover, it was concluded that the change in porosity and permeability by injection was more significant in low-porosity formations. Â© 2017 American Society of Civil Engineers.